Process optimization of glucose oxidase production by using locally isolated fungal strain - Adib Zubaidi Rashid (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
Glucose oxidase (D - oglucose oxygen 1- oxidoreductase EC 1.1.2.3.4) catalyzes the oxidation of D-glucose to gluconic acid, by utilizing molecular oxygen as an electron acceptor with simultaneous production of hydrogen peroxide. Effects of pH, temperature and agitation on the production of glucose oxidase from Aspergillus terreus were studied. The process conditions were optimized by using Central Composite Design approach. The experimental data obtained were fitted to a second - order polynomial equation using multiple regression analysis and analyzed by appropriate statistical methods. Glucose oxidase with the activity of 7.391 U/ml was produced at pH 6.5, 35 C and 250 rpm as the optimum conditions. Under these conditions, the experimental percentage error was 1.02 %, showing a close agreement with value predicted by the model